Heat-shrinkable film

By using a combination of a variety of resins and fine particles in the heat-shrinkable polyolefin film, the structure of the film is optimized, and the problems of insufficient heat shrinkability and high natural shrinkage in the prior art are solved, and efficient heat shrinkage and low natural shrinkage effects are achieved.

CN119630733APending Publication Date: 2025-03-14GUNZE LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380056005.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-03
Filing Date
2023-08-01
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing heat shrinkable polyolefin films have a low heat shrinkage rate at high temperatures and a high natural shrinkage rate, which is difficult to meet the needs of practical applications.

Method used

A core layer including petroleum resin, terpene resin and rosin resin is used, and combined with acrylic resin, cyclic olefin resin and ethylene resin, sealed pores are formed by fine particles, and the structure of the film is optimized to improve heat shrinkability and suppress natural shrinkage.

Benefits of technology

The heat shrinkage rate of the heat shrinkable film at high temperature is significantly improved, while the natural shrinkage rate is suppressed, meeting the needs of practical applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119630733A_ABST
    Figure CN119630733A_ABST
Patent Text Reader

Abstract

The heat-shrinkable film according to the present invention has: a first layer containing at least one of a petroleum resin, a terpene-based resin, and a rosin-based resin; a propylene resin; a cyclic olefin resin; and an ethylene-based resin having an ethylene component of 50 mol% or more and a melting point of 70 DEG C or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a heat shrinkable film. Background Art

[0002] Patent document 1 discloses a heat-shrinkable polyolefin film having good heat resistance and high transverse heat shrinkage, which is suitable as a base material for a label mounted on a bottle having a complex shape. According to patent document 1, the heat-shrinkable polyolefin film has at least a core layer and surface layers laminated on both sides of the core layer. The core layer contains: 54 wt% of an ethylene-propylene random copolymer having a Tm of 140°C; 8 wt% of an ethylene-butene random copolymer having a Tm of 66°C; 20 wt% of an ethylene-norbornene random copolymer having a Tg of 78°C and a norbornene content of 65 wt%; and 18 wt% of a hydrogenated petroleum resin having a softening point of 140°C.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application No. 2015-509861 Summary of the invention

[0006] Technical problem to be solved by the invention

[0007] However, the heat shrinkage rate (laterally) of the heat shrinkable polyolefin film of Patent Document 1 when immersed in hot water at 90°C for 10 seconds is about 40% to 43%, which is low for practical use. In addition, for such a heat shrinkable film, on the one hand, it is necessary to increase its heat shrinkage at high temperatures, and on the other hand, it is necessary to suppress its natural shrinkage rate in a general environment where heat shrinkage is not desired. Patent Document 1 does not take this into consideration.

[0008] An object of the present invention is to provide a heat shrinkable film in which the natural shrinkage is suppressed and the heat shrinkage at high temperature is improved.

[0009] Technical solutions for solving technical problems

[0010] The heat shrinkable film of the first aspect has the following first layer, which includes: at least one of a petroleum resin, a terpene resin and a rosin resin; a propylene resin; a cyclic olefin resin; and an ethylene resin having an ethylene component of 50 mol% or more and a melting point of 70°C or more.

[0011] The heat-shrinkable film according to a second aspect is the heat-shrinkable film according to the first aspect, wherein the first layer further contains fine particles, and in the first layer, closed pores are formed so as to surround the fine particles.

[0012] The heat shrinkable film according to a third aspect is the heat shrinkable film according to the first aspect or the second aspect, further comprising a second layer laminated on at least one surface side of the first layer and containing a thermoplastic resin.

[0013] The heat-shrinkable film according to the fourth aspect is a heat-shrinkable film according to any one of the first to third aspects, wherein, when the total amount of the thermoplastic resin contained in the first layer is set to 100 weight %, the first layer contains 10 weight % to 75 weight % of the propylene resin, and the Vicat softening temperature of the propylene resin is 90° C. or higher.

[0014] The heat-shrinkable film according to the fifth aspect is the heat-shrinkable film according to any one of the first to fourth aspects, wherein the first layer contains 10 wt % to 50 wt % of the propylene resin when the total amount of the thermoplastic resin contained in the first layer is 100 wt %.

[0015] The heat-shrinkable film according to the sixth aspect is the heat-shrinkable film according to any one of the first to fifth aspects, wherein the first layer contains 0.1% by weight to 65% by weight of the ethylene resin when the total amount of the thermoplastic resin contained in the first layer is 100% by weight.

[0016] The heat-shrinkable film according to a seventh aspect is the heat-shrinkable film according to any one of the first aspect to the sixth aspect, wherein the density of the ethylene-based resin is 0.88 g / cm 3 Above 0.95g / cm 3 the following.

[0017] The heat-shrinkable film according to an eighth aspect is the heat-shrinkable film according to any one of the first aspect to the seventh aspect, wherein the melting point of the ethylene-based resin is 75° C. or higher.

[0018] The heat-shrinkable film according to the 9th aspect is a heat-shrinkable film according to any one of the 1st aspect to the 8th aspect, wherein, when the total amount of the thermoplastic resin contained in the first layer is set to 100 weight %, the first layer contains 0.1 weight % to 85 weight % of the cyclic olefin resin, and the glass transition temperature of the cyclic olefin resin is 20° C. to 130° C.

[0019] The heat shrinkable film according to a tenth aspect is the heat shrinkable film according to any one of the first aspect to the ninth aspect, wherein the first layer contains 0.005 parts by weight or more and 1 part by weight of the fine particles based on 100 parts by weight of the total amount of the thermoplastic resin contained in the first layer.

[0020] The heat-shrinkable film according to an eleventh aspect is the heat-shrinkable film according to any one of the first aspect to the tenth aspect, wherein the mode particle size of the fine particles is 1 μm or more and 8 μm or less.

[0021] The heat-shrinkable film according to a twelfth aspect is the heat-shrinkable film according to any one of the first aspect to the eleventh aspect, wherein the density is 0.95 g / cm 3 the following.

[0022] The heat shrinkable film according to a thirteenth aspect is the heat shrinkable film according to any one of the first aspect to the twelfth aspect, wherein the haze is 10% or less.

[0023] The heat-shrinkable film according to a fourteenth aspect is the heat-shrinkable film according to any one of the first aspect to the thirteenth aspect, wherein the second layer comprises: at least one of a petroleum resin, a terpene resin, and a rosin resin; a cyclic olefin resin; an ethylene resin; and fine particles.

[0024] The heat-shrinkable film according to a fifteenth aspect is the heat-shrinkable film according to any one of the first aspect to the fourteenth aspect, wherein, when the thickness of the second layer is 1, the thickness of the first layer is 4 or more and 8 or less.

[0025] The heat-shrinkable label according to a sixteenth aspect includes the heat-shrinkable film according to any one of the first aspect to the fifteenth aspect.

[0026] Effects of the Invention

[0027] According to the present invention, there is provided a heat-shrinkable film in which the natural shrinkage is suppressed and the heat shrinkage at high temperature is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a cross-sectional view showing an example of the heat shrinkable film of the present invention.

[0029] Figure 2 This is a cross-sectional view showing an example of the heat shrinkable film of the present invention.

[0030] Figure 3A This is a microscopic photograph of a cross section of a layer containing microparticles.

[0031] Figure 3B This is a microscopic photograph of a layer cross section without particles. DETAILED DESCRIPTION

[0032] Hereinafter, one embodiment of the heat shrinkable film 10 of the present invention will be described. Figure 1 As shown in FIG. 1 , the heat shrinkable film 10 comprises at least a sheet-like core layer 1 (first layer) having a first surface and a second surface. Figure 2As shown, the heat shrinkable film 10 also has a surface layer 2 (second layer) laminated on at least one of the first and second surfaces of the core layer 1. That is, the heat shrinkable film 10 may be a single-layer structure having only the core layer 1, a two-layer structure having a surface layer 2 laminated on one side of the core layer 1, or a three-layer structure having a surface layer 2 laminated on both sides of the core layer 1. The dimensions in the figure do not necessarily reflect the actual dimensions. The following describes each component in detail.

[0033] <1-1. First example of core layer>

[0034] The core layer 1 contains a thermoplastic resin as a main component. The core layer 1 contains at least: a propylene resin; at least one of a petroleum resin, a terpene resin, and a rosin resin; a cyclic olefin resin; and an ethylene resin. In addition, microparticles may be contained. The structure of the core layer 1 according to the first example is described below.

[0035] [Acrylic resin]

[0036] The propylene resin is a resin containing 50 mol% or more of a propylene component. The propylene resin increases the elastic modulus and tensile strength of the heat shrinkable film 10. As the propylene resin, from the viewpoint of showing heat shrinkage, a propylene binary copolymer or a propylene ternary copolymer with propylene as the main component and α-olefin as the copolymer component is preferred, and a propylene ternary random copolymer is particularly preferred. As α-olefins, ethylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. can be cited. The ratio of α-olefin as the copolymer component is preferably 1 to 10 mol%. In addition, the propylene resin can also be a mixture of different propylene-α-olefin random copolymers. The propylene resin can contain long-chain branched polypropylene and a propylene elastomer.

[0037] The Vicat softening temperature of the propylene resin is preferably 90° C. or higher, more preferably 100° C. or higher, and further preferably 110° C. or higher. When the propylene resin is a mixed resin containing two or more propylene resins having different Vicat softening temperatures, the Vicat softening temperature of the propylene resin means an apparent Vicat softening temperature calculated by summing the product of the Vicat softening temperatures of the respective propylene resins and the blending ratio (weight ratio).

[0038] The melt flow rate (MFR) of the propylene resin at 230° C. is preferably 1.0 g / 10 min to 10.0 g / 10 min, more preferably 3.0 g / 10 min to 8.0 g / 10 min, and still more preferably 4.0 g / 10 min to 7.0 g / 10 min.

[0039] The density of the propylene resin is preferably 0.89 g / cm 3Above 0.93g / cm 3 the following.

[0040] When the entire thermoplastic resin contained in the core layer 1 is set to 100 weight %, the core layer 1 preferably contains the above-mentioned propylene resin in an amount of not less than 10 weight % and not more than 75 weight %, more preferably not less than 10 weight % and not more than 50 weight %, further preferably not less than 15 weight % and not more than 45 weight %, and particularly preferably not less than 20 weight % and not more than 40 weight %.

[0041] [Petroleum resin]

[0042] Petroleum resin improves the heat shrinkage of the heat shrinkable film 10. Petroleum resin is a resin obtained by polymerizing the C4-C5 fraction (mainly C5 fraction) or C5-C9 fraction (mainly C9 fraction) or a mixture thereof remaining after removing ethylene, propylene, butadiene, etc. by thermal decomposition of naphtha, for example, an alicyclic petroleum resin derived from cyclopentadiene or its dimer or an aromatic petroleum resin derived from the C9 component. From the viewpoint of suppressing the softening of the heat shrinkable film at temperatures below 100°C or ensuring transparency and rigidity, a hydrogenated alicyclic petroleum resin having a partially or completely hydrogenated alicyclic structure is preferred. In addition, even if it is a substance obtained by refining and polymerizing a single or multiple components in the C5 fraction or the C9 fraction, it can be used in the same manner.

[0043] Examples of commercially available products of the petroleum resins include I-Marv (manufactured by Idemitsu Kosan Co., Ltd.), Arkon (manufactured by Arakawa Chemical Industries, Ltd.), and Regalite (manufactured by Eastman Co., Ltd.).

[0044] The softening point of the petroleum resin is preferably 100°C to 150°C, more preferably 110°C to 140°C, and still more preferably 120°C to 130°C. By making the softening point of the petroleum resin within the above range, good heat shrinkage can be exhibited. In the case where the above petroleum resin is a mixed resin containing two or more petroleum resins with different softening points, the above softening point means an apparent softening point calculated by summing the product of the softening point of each petroleum resin and the blending ratio (weight ratio).

[0045] When the thermoplastic resin contained in the core layer 1 is set to 100% by weight as a whole, the core layer 1 preferably contains 10% by weight or more and 40% by weight or less of the above-mentioned petroleum resin, more preferably contains 15% by weight or more and 35% by weight or less, and further preferably contains 20% by weight or more and 30% by weight or less. By making the content of the petroleum resin within this range, the reduction of elongation at low temperature and the peeling between layers can be suppressed. In addition, in the case where the core layer 1 contains the terpene resin described below, the above range is applicable to the hydrocarbon resin composed of the combination of petroleum resin, terpene resin and rosin resin as a whole.

[0046] [Terpene resin, etc.]

[0047] The core layer 1 may contain hydrocarbon resins other than petroleum resins such as terpene resins and rosin resins in addition to petroleum resins, or may contain hydrocarbon resins other than petroleum resins such as terpene resins and rosin resins in place of petroleum resins. Examples of terpene resins include terpene resins from α-pinene or β-pinene, copolymers of α-pinene and β-pinene, aromatic modified terpene resins, terpene-phenolic resins, and hydrogenated terpene resins. Examples of rosin resins include gum rosin, wood rosin, tall-oil rosin, esterified rosin modified by glycerol or pentaerythritol, and hydrogenated rosin resins.

[0048] [Cyclic olefin resin]

[0049] The cyclic olefin resin improves both the heat shrinkability and rigidity of the heat shrinkable film 10. Since the cyclic olefin resin is an amorphous resin, the crystallinity of the heat shrinkable film can be reduced, and the stretchability during manufacturing can be improved. Examples of the cyclic olefin resin include: (a) a random copolymer of ethylene or propylene with a cyclic olefin, (b) a ring-opening polymer of the cyclic olefin or a copolymer with an α-olefin, (c) a hydrogenated product of the polymer of (b), and (d) a grafted modified product of (a) to (c) obtained using an unsaturated carboxylic acid and its derivatives.

[0050] The cyclic olefin is not particularly limited, and examples thereof include norbornene, 6-methyl norbornene, 6-ethyl norbornene, 5-propyl norbornene, 6-n-butyl norbornene, 1-methyl norbornene, 7-methyl norbornene, 5,6-dimethyl norbornene, 5-phenyl norbornene, 5-benzyl norbornene and their derivatives. Furthermore, tetracyclododecene, 8-methyltetracyclo-3-dodecene, 8-ethyltetracyclo-3-dodecene, 5,10-dimethyltetracyclo-3-dodecene and their derivatives can be mentioned. The α-olefin is as described above.

[0051] Examples of commercially available products of the cyclic olefin resins include APEL (manufactured by Mitsui Chemicals, Inc.), TOPAS COC (manufactured by Polyplastics Co., Ltd.), and ZEONOR (manufactured by Zeon Corporation).

[0052] The number average molecular weight of the cyclic olefin resin measured by GPC (gel permeation chromatography) is preferably 1000 or more and preferably 1,000,000 or less. When the molecular weight is within the above range, film formation is easy.

[0053] The melt volume rate (MVR) of the cyclic olefin resin at 230°C is preferably 2 cm 3 / 15cm over 10 minutes 3 / 10 minutes or less, more preferably 3cm 3 / 14cm over 10 minutes 3 / 10 minutes or less, more preferably 4cm 3 / 13cm over 10 minutes 3 / Less than 10 minutes.

[0054] The glass transition temperature of the cyclic olefin resin is preferably 20°C to 130°C, more preferably 50°C to 100°C. If the glass transition temperature is 20°C or higher, the heat resistance of the heat-shrinkable film can be improved, and natural shrinkage can be suppressed. On the other hand, if the glass transition temperature is 130°C or lower, the heat shrinkage rate of the heat-shrinkable film in the main shrinkage direction can be sufficiently increased. In the case where the cyclic olefin resin is a mixed resin containing two or more cyclic olefin resins with different glass transition temperatures, the glass transition temperature means the apparent glass transition temperature calculated by summing the product of the glass transition temperature of each cyclic olefin resin and the mixing ratio (weight ratio).

[0055] The density of the cyclic olefin resin is preferably 1.00 g / cm 3 Above 1.05g / cm 3 Below, more preferably 1.01 g / cm 3 Above 1.04g / cm 3 the following.

[0056] When the entire thermoplastic resin contained in the core layer 1 is set to 100 weight %, the core layer 1 preferably contains 0.1 weight % to 85 weight % of the above-mentioned cyclic olefin resin, more preferably 1 weight % to 80 weight %, and further preferably 5 weight % to 75 weight %.

[0057] [Vinyl resin]

[0058] Ethylene resin is a resin containing 50 mol% or more of ethylene components. Ethylene resin can improve the impact strength of the heat shrinkable film 10, and when used for the outer layer such as the surface layer 2, it can improve the resistance of the heat shrinkable film 10 to sebum whitening. As ethylene resin, branched low-density polyethylene, linear low-density polyethylene, ethylene-vinyl acetate copolymer, ionomer resin, and mixtures thereof can be listed. In addition, ethylene copolymers with ethylene as the main component and α-olefin as the copolymer component can also be listed. The above copolymers can be random copolymers or block copolymers. As α-olefins, α-olefins with 3 to 20 carbon atoms can be listed, specifically, for example, propylene, 1-butene, 3-methyl-1-butene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, etc. can be listed. The ratio of the α-olefin as a copolymer component is preferably 1 to 25 mol%. In addition, the ethylene-based resin may be a mixture of different ethylene-α-olefin random copolymers. Furthermore, the ethylene-based resin may contain an ethylene-based elastomer.

[0059] The density of the ethylene resin is preferably 0.88 g / cm 3 Above 0.95g / cm 3 the following.

[0060] The melting point of the ethylene resin is preferably 70° C. or higher, more preferably 75° C. or higher, and further preferably 80° C. or higher. By setting the melting point of the ethylene resin to be higher than the lower limit, the natural shrinkage rate of the heat-shrinkable film 10 can be suppressed. In addition, the Vicat softening temperature of the ethylene resin is preferably 80° C. or higher, more preferably 85° C. or higher, and further preferably 90° C. or higher. When the ethylene resin is a mixed resin containing two or more ethylene resins having different melting points, the melting point means the melting point of the resin with the highest melting point among the ethylene resins.

[0061] The melt flow rate (MFR) of the ethylene resin at 190°C is preferably 0.5 g / 10 min to 5 g / 10 min, more preferably 0.7 g / 10 min to 3 g / 10 min, further preferably 0.9 g / 10 min to 2 g / 10 min.

[0062] When the entire thermoplastic resin contained in the core layer 1 is set to 100 weight %, the core layer 1 preferably contains 0.1 weight % to 65 weight % of the above-mentioned ethylene resin, more preferably 1 weight % to 60 weight %, and further preferably 2 weight % to 55 weight %.

[0063] [particle]

[0064] The core layer 1 may contain particles 3 in addition to the above-mentioned thermoplastic resin. The particles 3 may be particles from recycled materials or particles newly added when forming the core layer 1. As recycled materials, for example, a heat-shrinkable film having a thermoplastic resin as a main component and further containing particles 3 as an anti-blocking agent may be cited.

[0065] Figure 3A is a microscopic photograph of a cross section of the core layer 1 (the central part in the vertical direction) including the microparticle 3. Figure 3B This is a microscopic photograph of a cross section of the core layer 1 (the center portion in the vertical direction) that does not contain fine particles. Figure 3A The core layer 1 shown is compounded with 2 parts by weight of the microparticles 3 in order to more clearly show the behavior of the microparticles 3 or the thermoplastic resin. Figure 3A and Figure 3B It can be seen that when the core layer 1 includes the particles 3 as described above and is stretched, Figure 3A As shown, closed pores 4 surrounding the particles 3 are formed in the core layer 1 . Figure 3A The diameter of the particles 3 is 3 to 6 μm, and the size of the closed pores 4 is about 6 μm in the thickness direction of the core layer 1 (the up-down direction in the figure) and about 10 μm in the surface direction (the left-right direction in the figure).

[0066] The space formed around the microparticles 3 by closing the pores 4 further reduces the density of the core layer 1, making it easier to perform gravity separation when recycling the heat shrinkable film 10. In this way, the heat shrinkable film 10 can be configured to not only contain recycled raw materials but also be easily recyclable.

[0067] As microparticles 3, any of organic microparticles or inorganic microparticles can be used. As organic microparticles, organic microparticles such as acrylic resin microparticles, styrene resin microparticles, styrene-acrylic resin microparticles, polyurethane resin microparticles, and silicone resin microparticles can be used. These can be cross-linked or not, but in order to improve the heat resistance of the microparticles, it is more desirable to be cross-linked. Among them, from the viewpoint of compatibility with the above-mentioned cyclic olefin resin, acrylic resin microparticles are preferably used, and polymethyl methacrylate cross-linked microparticles are further preferably used. In addition, among the above-mentioned organic microparticles, as commercially available products, for example, Techpolymer (manufactured by Sekisui Chemicals Co., Ltd.), Finesphere (manufactured by Nippon Paint Co., Ltd.), Ganzpearl (manufactured by Aica Kogyo Co., Ltd.), Art-pearl (manufactured by Gengami Kogyo Co., Ltd.), etc. can be cited.

[0068] As the inorganic fine particles, for example, silica, zeolite, alumina, etc. can be used. In addition, the fine particles may be constituted as hollow glass balloons or may be constituted as a porous body.

[0069] The mode frequency particle size of the microparticles 3 is preferably, for example, not less than 1 μm and not more than 8 μm, more preferably not less than 2 μm and not more than 7 μm, and further preferably not less than 3 μm and not more than 6 μm. The mode frequency particle size can be measured by a known laser diffraction-scattering method or the like. By setting the mode frequency particle size of the microparticles 3 to the above range, aggregation can be suppressed, the haze value of the heat shrinkable film 10 is not easily increased, and smoothness can be maintained. In addition, from the viewpoint of surely forming the closed pores 4, the mode frequency particle size of the microparticles 3 is preferably sufficiently small relative to the thickness of the core layer 1. In addition, the microparticles 3 may include two or more microparticles with different mode frequency particle sizes.

[0070] When the total amount of the thermoplastic resin contained in the core layer 1 is 100 parts by weight, the core layer 1 preferably contains 0.005 parts by weight to 1 part by weight of the above-mentioned microparticles, more preferably 0.01 parts by weight to 1 part by weight, and further preferably 0.03 parts by weight to 0.8 parts by weight. By setting the content of the microparticles 3 to be greater than the above lower limit, closed pores 4 can be generated to a degree sufficient to reduce the density of the heat shrinkable film 10. On the other hand, by setting the content of the microparticles 3 to be less than the above upper limit, it is possible to avoid light scattering in the closed pores 4, which can prevent the haze of the heat shrinkable film 10 from increasing excessively.

[0071] <1-2. Second example of core layer>

[0072] In the case where the core layer 1 includes the above-mentioned microparticles 3, the core layer 1 may be configured according to the second example described below instead of the first example. The core layer 1 according to the second example includes at least: propylene resin; at least one of petroleum resin, terpene resin and rosin resin; cyclic olefin resin; ethylene resin; and microparticles. The following mainly describes the differences from the first example.

[0073] [Acrylic resin]

[0074] The specific example of the propylene resin is as described in the first example, but in the second example, the Vicat softening temperature of the propylene resin is preferably 60° C. or higher, more preferably 90° C. or higher, and further preferably 100° C. or higher. When the propylene resin is a mixed resin containing two or more propylene resins having different Vicat softening temperatures, the Vicat softening temperature of the propylene resin means the apparent Vicat softening temperature calculated by summing the product of the Vicat softening temperature of each propylene resin and the blending ratio (weight ratio).

[0075] Furthermore, the MFR of the propylene resin at 230°C is preferably 1.0 g / 10 min to 12.0 g / 10 min, more preferably 2.0 g / 10 min to 10.0 g / 10 min, and still more preferably 2.5 g / 10 min to 8.0 g / 10 min.

[0076] Furthermore, the density of the propylene resin is preferably 0.86 g / cm 3 Above 0.93g / cm 3 the following.

[0077] When the entire thermoplastic resin contained in the core layer 1 is set to 100 weight %, the core layer 1 according to the second example preferably contains the above-mentioned propylene resin in an amount of not less than 10 weight % and not more than 75 weight %, more preferably not less than 15 weight % and not more than 50 weight %, and further preferably not less than 20 weight % and not more than 45 weight %.

[0078] [Hydrocarbon resin]

[0079] The hydrocarbon resins, namely, petroleum resins, terpene resins, and rosin resins are as described in the first example, and thus description thereof will be omitted.

[0080] [Cyclic olefin resin]

[0081] The cyclic olefin resin is also as described in the first example, and therefore the description thereof is omitted.

[0082] [Vinyl resin]

[0083] Specific examples of the ethylene resin, the preferred range of density, and the preferred range of content are as described in the first example. In the second example, the melting point of the ethylene resin is preferably 50° C. or higher, more preferably 60° C. or higher, and further preferably 75° C. or higher. By setting the melting point of the ethylene resin to be above the above lower limit, the natural shrinkage rate of the heat-shrinkable film 10 can be suppressed. In addition, the Vicat softening temperature of the ethylene resin is preferably 45° C. or higher, more preferably 50° C. or higher, and further preferably 52.5° C. or higher.

[0084] Furthermore, the MFR of the ethylene resin at 190°C is preferably 0.5 g / 10 min to 10 g / 10 min, more preferably 0.7 g / 10 min to 8 g / 10 min, and still more preferably 0.9 g / 10 min to 7 g / 10 min.

[0085] [particle]

[0086] Specific examples of the microparticles 3 and the preferred range of the mode particle size are as described in the first example. In the second example, when the total amount of the thermoplastic resin contained in the core layer 1 is 100 parts by weight, the core layer 1 preferably contains 0.005 parts by weight to 3 parts by weight of the microparticles, more preferably 0.01 parts by weight to 2 parts by weight, and further preferably 0.03 parts by weight to 1 part by weight. By setting the content of the microparticles 3 to be greater than the above lower limit, closed pores 4 can be generated to a degree sufficient to reduce the density of the heat shrinkable film 10. On the other hand, by setting the content of the microparticles 3 to be less than the above upper limit, it is possible to avoid light scattering in the closed pores 4, which may cause the haze of the heat shrinkable film 10 to increase excessively.

[0087] <1-3.Thickness of core layer>

[0088] The thickness of the core layer 1 according to the first example and the second example is preferably 10 μm to 80 μm, more preferably 15 μm to 70 μm, and further preferably 20 μm to 60 μm. In addition, in the following description, when applicable to either of the core layers 1 according to the first example and the second example, they are not particularly distinguished and are simply referred to as "core layer 1".

[0089] <2. Surface>

[0090] The surface layer 2 contains a thermoplastic resin as a main component. As the thermoplastic resin, styrene resins, ester resins, olefin resins, etc. can be listed, wherein olefin resins are preferably used. In addition, the surface layer 2 may also contain microparticles as an anti-blocking agent. Main olefin resins such as ethylene resins, propylene resins, petroleum resins, terpene resins, rosin resins, and cyclic olefin resins, and microparticles are as described above.

[0091] The surface layer 2 preferably contains at least one of a petroleum resin, a terpene resin, and a rosin resin; a cyclic olefin resin; an ethylene resin; and microparticles. Thus, the heat shrinkable film 10 having the core layer 1 and the surface layer 2 can be easily used as a recycled raw material for the heat shrinkable film 10. In addition, these olefin resins and microparticles can use the same composition as the core layer 1, or different compositions. In the case where the core layer 1 and the surface layer 2 are adjacent and both contain a cyclic olefin resin, the bonding strength between the layers is improved. In addition, in the case where the surface layer 2 contains an ethylene resin, the resistance to sebum whitening is improved.

[0092] The surface layer 2 is not limited thereto, and preferably, when the thermoplastic resin contained in the surface layer 2 is set to 100% by weight as a whole, it contains the above-mentioned hydrocarbon resin (petroleum resin, terpene resin and rosin resin) of 0.1% by weight or more and 25% by weight or less, more preferably contains 1% by weight or more and 20% by weight or less, and further preferably contains 5% by weight or more and 15% by weight or less. Similarly, the surface layer 2 preferably contains the above-mentioned cyclic olefin resin of 65% by weight or more and 95% by weight or less, more preferably contains 70% by weight or more and 90% by weight or less, and further preferably contains 75% by weight or more and 85% by weight or less. In addition, the surface layer 2 preferably contains the above-mentioned ethylene resin of 0.1% by weight or more and 30% by weight or less, more preferably contains 1% by weight or more and 25% by weight or less, and further preferably contains 5% by weight or more and 20% by weight or less.

[0093] When the total amount of the thermoplastic resin contained in the surface layer 2 is 100 parts by weight, the surface layer 2 preferably contains 0.01 parts by weight to 1 part by weight of the above-mentioned fine particles, more preferably 0.03 parts by weight to 0.8 parts by weight, and further preferably 0.05 parts by weight to 0.5 parts by weight.

[0094] [Thickness of surface layer]

[0095] The thickness of the surface layer 2 is preferably 1 μm to 25 μm, more preferably 2.5 μm to 20 μm, and even more preferably 5 μm to 15 μm. When the thickness of the surface layer 2 is 1, the thickness of the core layer 1 is preferably 4 to 8, and more preferably 5 to 7.

[0096] <3. Other ingredients>

[0097] In addition, additives such as antioxidants, heat stabilizers, ultraviolet absorbers, light stabilizers, lubricants, antistatic agents, flame retardants, antibacterial agents, fluorescent brighteners, colorants, etc. may be added to at least one of the core layer 1 and the surface layer 2 as needed.

[0098] <4. Thickness of heat shrinkable film>

[0099] The overall thickness of the heat shrinkable film 10 is preferably, for example, 10 μm to 80 μm, more preferably 15 μm to 70 μm, and further preferably 20 μm to 60 μm. If the overall thickness of the heat shrinkable film 10 is within the above range, excellent heat shrinkability can be obtained, and the shape tracking property when installed on the container becomes good, and it can be suitably used as a base film for a heat shrinkable label.

[0100] <5. Heat shrinkage properties of heat shrinkable film>

[0101] The heat shrinkage rate in the main shrinkage direction when the heat shrinkable film 10 is immersed in hot water at 90° C. for 10 seconds is preferably 55% or more. In addition, the heat shrinkage rate in the main shrinkage direction when immersed in hot water at 98° C. for 10 seconds is preferably 65% ​​or more. If the heat shrinkage rate is above the upper limit, problems such as poor shrinkage will not occur, and the film can be suitably used as a heat shrinkable film.

[0102] <6. Natural shrinkage rate of heat shrinkable film>

[0103] When the heat shrinkable film 10 is left in a thermostat at 40°C for 7 days, the natural shrinkage in the main shrinkage direction is preferably 2% or less, and the natural shrinkage in the direction orthogonal to the main shrinkage direction (hereinafter also referred to as "secondary shrinkage direction") is preferably 0.3% or less.

[0104] <7. Method for producing heat shrinkable film>

[0105] The method for manufacturing the heat shrinkable film 10 is not particularly limited. When the heat shrinkable film 10 has a multi-layer structure, it is preferably a method in which each layer is simultaneously molded by a coextrusion method. When the coextrusion method is a T-die-based coextrusion method, the lamination method may be a feed block method, a multi-manifold method, or a method using any of these methods in combination.

[0106] As a method for manufacturing the heat shrinkable film 10, specifically, for example, the following method can be cited: the raw materials constituting the core layer 1 and the surface layer 2 are respectively put into an extruder, extruded into a sheet by a die head, cooled and solidified by a winding roller, and then stretched along a single axis or a double axis, preferably along a double axis. As the above-mentioned stretching method, for example, a roll stretching method, a tenter stretching method, or a combination thereof can be used. The stretching temperature is changed according to the softening temperature of the resin constituting the film, the shrinkage characteristics required for the heat shrinkable film 10, etc., and is preferably below 140°C, and more preferably below 120°C.

[0107] The stretching ratio in the main shrinking direction is changed according to the resin constituting the film, the stretching means, the stretching temperature, etc., and is preferably 3 times or more and 7 times or less, and more preferably 4 times or more and 6 times or less. In addition, the stretching ratio in the secondary shrinking direction is preferably 1.1 times or more and 1.5 times or less, and more preferably 1.2 times or more and 1.4 times or less.

[0108] When the core layer 1 includes the fine particles 3, by setting the stretching temperature and the stretching ratio as described above, closed pores can be effectively formed around the fine particles, and the density of the heat shrinkable film 10 can be easily controlled.

[0109] <8. Applications of heat shrinkable films>

[0110] The use of the heat shrinkable film 10 is not particularly limited, and it is suitable for use as a base film for heat shrinkable labels mounted on containers such as PET bottles and metal cans. In this case, the heat shrinkable film 10 is laminated with a printed layer of a label design on at least one surface, cut into a predetermined size, or center-sealed to form a tubular heat shrinkable label.

[0111] <9. Other forms of heat shrinkable films>

[0112] In the above description, the heat shrinkable film 10 is a single-layer structure having only the core layer 1, or a two-layer or three-layer structure having the surface layer 2 laminated on at least one of the first surface and the second surface of the core layer 1. However, the heat shrinkable film 10 is not limited thereto, and may further have a layer laminated on the surface layer 2, or may further have a layer laminated between the core layer 1 and the surface layer 2. That is, the heat shrinkable film 10 may be a four-layer structure or a five-layer structure.

[0113] <10. Features>

[0114] The heat-shrinkable film 10 has a core layer 1 including propylene resin, hydrocarbon resin, cyclic olefin resin and ethylene resin with a relatively high melting point, and has high heat shrinkage in hot water above 90°C, while its natural shrinkage is suppressed. Therefore, when the heat-shrinkable film 10 is configured as a tubular heat-shrinkable label, it can easily follow the shape of the container to be installed, and the gap between the container and the heat-shrinkable label can be suppressed, so that good installation performance can be achieved. In addition, the diameter of the tubular heat-shrinkable label becomes smaller due to natural shrinkage, and it is not easy to cause the problem of not being able to cover the container. Furthermore, natural shrinkage is also suppressed in the secondary shrinkage direction, thereby minimizing the area of ​​the heat-shrinkable label cut out from the heat-shrinkable film 10 and improving the yield. As described above, a heat-shrinkable label including a heat-shrinkable film 10 also falls within the scope of the present invention.

[0115] The core layer 1 may contain recycled raw materials from a resin film containing propylene resin, hydrocarbon resin, cyclic olefin resin or ethylene resin. Cyclic olefin resin increases thermal shrinkage and rigidity, and ethylene resin increases impact strength. The core layer 1 may further contain microparticles 3. The microparticles 3 generate closed pores in the core layer 1 having a thickness sufficiently larger than the diameter of the microparticles 3, making it easy to set the density of the heat shrinkable film 10 to less than 1 g / cm 3 , preferably 0.95g / cm 3 Therefore, it is possible to provide a material that is easy to use with a density exceeding 1 g / cm 3The heat shrinkable film 10 can be separated from the styrene resin film or ester resin film and can be easily recycled. The heat shrinkable film 10 can also contain environmentally friendly materials other than the recycled raw materials from the above-mentioned resin film, and substantially all resin components can also be composed of environmentally friendly materials.

[0116] As the above-mentioned materials for reducing environmental load, for example, materials derived from biomass and materials obtained by chemically recycling the resin film including the heat shrinkable film 10 and the intermediate materials for its production are included. In addition, materials obtained by mechanical recycling are also included, for example, materials obtained by crushing the resin film including the heat shrinkable film 10 and the intermediate materials for its production to form fluff having only a thermal history during film making, or materials obtained by regenerating particles by giving it a thermal history again. The intermediate materials for production include the resin film obtained by deinking the unqualified materials in the printing step, the leftover materials of the resin film, the cutting scraps, and the resin composition generated during extrusion without being formed into a resin film. The amount of the above-mentioned materials for reducing environmental load can be allocated to the heat shrinkable film 10 according to the mass balance method.

[0117] [Example]

[0118] Hereinafter, examples of the present invention will be described in detail, but the present invention is not limited to these examples.

[0119] <1. Preparation of Examples and Comparative Examples>

[0120] The heat shrinkable films of Examples 1 to 12 and Comparative Examples were prepared as follows. Figure 2 As shown in FIG. 1 , these heat shrinkable films have a three-layer structure including a core layer and skin layers laminated on both sides of the core layer. The materials used for the core layer and the skin layers are as follows.

[0121] (1) Propylene resin (PP): Density 0.9 g / cm based on JIS K7112 3 , MFR 5.5 g / 10 min at 230°C, Vicat softening temperature 111°C based on ISO 306, melting point 132°C based on ISO 11357-3.

[0122] (2) Cyclic olefin resin (COC): Density 1.01 g / cm based on JIS K7112 3 , MVR 12cm at 230℃ 3 / 10 minutes, glass transition temperature 78°C based on ISO 11357-1,2,3.

[0123] (3) Petroleum resin: Density 0.98 g / cm based on JIS K7112 3 , the softening point based on JIS K6863 (ring and ball method) is 125°C.

[0124] (4) Ethylene resin: a copolymer of ethylene and 1-hexene containing 50 mol% or more of ethylene components, with a density of 0.915 g / cm based on JIS K7112 3 , MFR at 190°C based on JIS K7210 is 1.0 g / 10 min, Vicat softening temperature based on JIS K7206 is 98°C, and melting point based on JIS K7121 is 118°C.

[0125] (5) Microparticles: Made of cross-linked polymethyl methacrylate resin (PMMA), with a mode diameter of 4 μm based on particle size distribution measured using a laser diffraction particle size distribution analyzer (LA-500, manufactured by Horiba, Ltd.).

[0126] These were mixed in the ratios shown in Table 1 to obtain raw material compositions constituting the core layers and the skin layers of Examples 1 to 12 and Comparative Examples.

[0127] Next, the raw material composition constituting the core layer and the surface layer was melted using an extruder, the core layer was melted at a barrel temperature of 200°C, the surface layer was melted at a barrel temperature of 220°C, extruded from a T-die, and cooled and solidified using a roller cooled to 30°C to produce an unstretched sheet. The unstretched sheet was stretched 6 times in the TD (Transverse direction) direction and 1.2 times in the MD (Machine direction) direction using a tenter stretching machine at a temperature of 120°C to produce a heat-shrinkable film having a thickness ratio shown in Table 1. Hereinafter, the main shrinkage direction of the heat-shrinkable film is also referred to as the TD direction, and the secondary shrinkage direction is also referred to as the MD direction.

[0128] [Table 1]

[0129]

[0130] <2. Evaluation>

[0131] The heat shrinkable films of Examples 1 to 12 and Comparative Examples were evaluated as follows.

[0132] <2-1. Thermal shrinkage>

[0133] Cut the same number of samples of 100 mm in MD direction × 100 mm in TD direction from each heat shrinkable film. Immerse each sample in hot water at the following temperature for 5 seconds or 10 seconds, then take it out, immerse it in water at 20°C for 10 seconds, and take it out again. Then, measure the length L1 (mm) in MD direction and the length L2 (mm) in TD direction of each sample, and calculate the shrinkage (%) in MD direction and TD direction according to the following formula. For each heat shrinkable film, the average shrinkage of the samples is taken as the heat shrinkage.

[0134] Shrinkage rate (%) = {(100-L) / 100} × 100 (L = L1, L2)

[0135] Hot water was used at 70°C, 80°C, 90°C, and 98°C. Five samples of each heat shrinkable film were prepared and immersed for 5 seconds and 10 seconds, and the heat shrinkage in the MD direction and TD direction was calculated. The heat shrinkage in the TD direction was evaluated as follows.

[0136] (1) Immersed in hot water at 90°C for 10 seconds: 55% or more is good, and less than 55% is bad.

[0137] (2) Immersed in hot water at 98°C for 10 seconds: 65% or more is good, and less than 65% is bad.

[0138] <2-2. Natural shrinkage rate>

[0139] Cut the same number of samples of 100mm in MD direction × 100mm in TD direction from each heat shrinkable film. After each sample was left to stand in a thermostat (manufactured by Yamato Scientific, IL-82) at 30°C or 40°C for 7 days, the length L1 (mm) in MD direction and the length L2 (mm) in TD direction of each sample were measured respectively, and the shrinkage rate (%) was calculated according to the same formula as the heat shrinkage rate. For each heat shrinkable film, the average value of the shrinkage rate of the sample was taken as the natural shrinkage rate. Two samples were made for each temperature.

[0140] The natural shrinkage at 40°C was evaluated as follows.

[0141] (1) TD direction: less than 2% is good, more than 2% is bad

[0142] (2) MD direction: 0.3% or less is good, more than 0.3 is bad

[0143] <2-3. Young's modulus>

[0144] Five samples of 250 mm in MD direction and 5 mm in TD direction and five samples of 250 mm in TD direction and 5 mm in MD direction were cut from the heat-shrinkable films of Examples 1 to 3 and Comparative Examples, respectively. For these samples, the Young's modulus (GPa) in the MD direction and the TD direction was measured by the method according to ASTM D882 using a Strograph (manufactured by Toyo Seiki Seisaku-sho, Ltd., VE-1D). For each heat-shrinkable film, the average value of each direction of the sample was taken as the Young's modulus in each direction.

[0145] Young's modulus was evaluated as follows.

[0146] (1) 1.6 GPa or more in the MD direction and 2.2 GPa or more in the TD direction: good.

[0147] (2) The above conditions are not met: defective.

[0148] <2-4. Shrinkage stress>

[0149] Samples of 10 mm in MD direction and 200 mm in TD direction were cut from each heat shrinkable film. For these samples, one end in TD direction was fixed with a distance of 100 mm between the clamps, and the other end was connected to a load cell for measuring the load. After that, the sample was immersed in 80°C hot water together with the clamp for 30 seconds to make it heat shrink, and the shrinkage stress (N / 10mm) was measured at the beginning of the immersion and 30 seconds after. For each heat shrinkable film, the average value of the sample was taken as the shrinkage stress.

[0150] <2-5. Haze>

[0151] Four samples of 50 mm x 100 mm were cut from each heat shrinkable film. The haze (%) of each sample was measured using a haze meter (NDH5000 manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K-7136. The average value of the samples for each heat shrinkable film was taken as the haze.

[0152] <2-6. Density>

[0153] Four samples of 50 mm × 100 mm were cut from the heat-shrinkable films of Examples 4 to 12. The density (g / cm2) of these samples was measured using a dry automatic densitometer (manufactured by Shimadzu Corporation, 1345-100CC) according to JIS Z8837 (2018). 3 ). For the heat shrinkable film, the average value of the samples was taken as the density.

[0154] <3. Evaluation results>

[0155] Table 2 shows the evaluation results.

[0156] [Table 2]

[0157]

[0158] According to the above results, Examples 1 to 12 have sufficient quality in terms of heat shrinkage and natural shrinkage. In contrast, in the comparative example in which the core layer does not contain cyclic olefin resin and ethylene resin, the heat shrinkage in 90°C hot water and 98°C hot water (10 seconds) and the natural shrinkage at 40°C are poor. In addition, it was confirmed that the Young's modulus was good in Examples 1 to 3, while it was confirmed that the Young's modulus was also poor in the comparative example. According to the results of Examples 4 to 12, it was confirmed that if the proportion of microparticles contained in the core layer is small, the effect on the haze is small, and if the proportion is large, the density can be reduced. In particular, it was confirmed that if the content of microparticles in the core layer is set to less than 1 part by weight, the haze is maintained below 10%.

[0159] Explanation of symbols

[0160] 1: core layer (first layer); 2: surface layer (second layer); 3: microparticles; 4: closed pores; 10: heat shrinkable film.

Claims

1. A heat shrinkable film, characterized in that: Having the following first layer, This first layer contains: At least one of petroleum resin, terpene resin and rosin resin; Acrylic resin; Cyclic olefin resin; and An ethylene resin having an ethylene content of 50 mol% or more and a melting point of 70°C or more.

2. The heat shrinkable film according to claim 1, characterized in that: The first layer further includes fine particles, and in the first layer, closed pores are formed so as to surround the fine particles.

3. The heat shrinkable film according to claim 1 or 2, characterized in that: The invention further includes a second layer which is laminated on at least one surface side of the first layer and contains a thermoplastic resin.

4. The heat-shrinkable film according to claim 1 or 2, characterized in that: When the total amount of the thermoplastic resin contained in the first layer is 100 wt %, the first layer contains 10 wt % or more and 75 wt % or less of the propylene resin. The propylene resin has a Vicat softening temperature of 90° C. or higher.

5. The heat shrinkable film according to claim 4, characterized in that: When the entire amount of the thermoplastic resin contained in the first layer is 100% by weight, the first layer contains 10% by weight or more and 50% by weight or less of the propylene-based resin.

6. The heat shrinkable film according to claim 1 or 2, characterized in that: When the entire amount of the thermoplastic resin contained in the first layer is set to 100 wt %, the first layer contains 0.1 wt % to 65 wt % of the ethylene-based resin.

7. The heat shrinkable film according to claim 1 or 2, characterized in that: The density of the ethylene resin is 0.88 g / cm 3 Above 0.95g / cm 3 the following.

8. The heat shrinkable film according to claim 1 or 2, characterized in that: The melting point of the ethylene resin is 75° C. or higher.

9. The heat shrinkable film according to claim 1 or 2, characterized in that: When the entire thermoplastic resin contained in the first layer is set to 100 wt %, the first layer contains 0.1 wt % to 85 wt % of the cyclic olefin resin. The cyclic olefin resin has a glass transition temperature of 20° C. or higher and 130° C. or lower.

10. The heat shrinkable film according to claim 2, characterized in that: The first layer contains 0.005 parts by weight or more and 1 part by weight or less of the fine particles, based on 100 parts by weight of the entire thermoplastic resin contained in the first layer.

11. The heat shrinkable film according to claim 2 or 10, characterized in that: The mode particle size of the microparticles is not less than 1 μm and not more than 8 μm.

12. The heat-shrinkable film according to claim 1 or 2, characterized in that: Density: 0.95g / cm 3 the following.

13. The heat shrinkable film according to claim 1 or 2, characterized in that: The haze is 10% or less.

14. The heat shrinkable film according to claim 3, characterized in that: The second layer comprises: At least one of petroleum resin, terpene resin and rosin resin; Cyclic olefin resins; Vinyl resins; and particle.

15. The heat shrinkable film according to claim 3, characterized in that: When the thickness of the second layer is set to 1, the thickness of the first layer is greater than or equal to 4 and less than or equal to 8.

16. A heat shrinkable label, characterized in that: The heat-shrinkable film according to claim 1 or 2 is included.

Citation Information

Patent Citations

  • Heat-shrinkable polyolefin films and methods for producing the same

    JP2015509861A